La réplique d’expérience en musique : la question de la jouabilité des instruments au musée de la Musique - Marie-Anne Loeper-Attia (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The replicas of experiments or facsimiles are options that are frequently used in valorising musical heritage. Nonetheless, the notion of musical authenticity is quite complex and reconstructing as best one can an instrument is insufficient to bring a sound back to life. If the potential sounds can be understood, sound quality is much more subjective. The question will be treated here using a variety of modern and contemporary musical instruments, including a Fender Stratocaster electric guitar, Martenot Waves and a Max Mathews aluminium violin.